Moth Bean, Gelatin, and Murraya Koenigii Leaves Extract-Based Film and Coating: Effect of Coating on Shelf and Quality of Solanum Melongena - Raj Kumar; Naina Gautam; Shashikant Yadav; Venkatesh Thulasiraman; Anil Yadav; Nasir Awol (Journal of Food Quality)
Moth bean starch (MS), gelatin (GA), and Murraya koenigii leaves extract (ME) are blended at different compositions to prepare film and coating according to casting and dipping approaches. Different MS, GA, and ME compositions were used to synthesize films and coating. The film compositions (MS : GA: ME: 60 : 20 : 20 and MS : GA: ME:20 : 60 : 20) were represented in terms of F3 and F4, respectively. The results showed that F3 exhibited better physicochemical properties than other films. In addition, SEM images showed that all components of the films were uniformly mixed and formed smooth surface morphology without cracks and bubbles. FTIR results indicate that ME in the films induces interactions between the film components, causing an improvement in compactness. Moreover, an optimized film-forming solution was tested as a coating. Parameters such as skin tightness, weight loss, pH, titratable acidity, and sensory analysis were considered to check the quality of coated Solanum melongena during storage. The results show that the formulation effectively maintains the quality parameters during storage. Furthermore, it also notices that coating extends the shelf life of Solanum melongena by one week.